Can the Central Compact Object in HESS J1731–347 Be Indeed the Lightest Neutron Star Observed? - S. R. Zhang; J. A. Rueda Hernandez; R. Negreiros (The Astrophysical Journal)
The exceptionally low mass of $0.7{7}_{-0.17}^{+0.2}{M}_{\odot }$ for the central compact object (CCO) XMMU J173203.3–344518 (XMMU J1732) in the supernova remnant (SNR) HESS J1731–347 challenges standard neutron star (NS) formation models. The nearby post–asymptotic giant branch star IRAS 17287–3443 (≈​​​​​​0.6 M _⊙ ), also within the SNR, enriches the scenario. To address this puzzle, we advance the possibility that the gravitational collapse of a rotating presupernova (SN) iron core (≈1.2 M _⊙ ) could result in a low-mass NS. We show that angular momentum conservation during the collapse of an iron core rotating at ≈45% of the Keplerian limit results in a mass loss of ≈0.3 M _⊙ , producing a stable newborn NS of ≈0.9 M _⊙ . Considering the possible spin-down, this indicates that the NS is now slowly rotating, thus fulfilling the observed mass–radius relation. Additionally, the NS's surface temperature (≈2 × 10 ^6 K) aligns with canonical thermal evolution for its ≈4.5 kyr age. We propose the pre-SN star, likely an ultrastripped core of ≈4.2 M _⊙ , formed a tidally locked binary with IRAS 17287–3443, with a 1.43 day orbital period. The SN led to a ≈3 M _⊙ mass loss, imparting a kick velocity ≲670 km s ^−1 , which disrupted the binary. This scenario explains the observed 0.3 pc offset between XMMU J1732 and IRAS 17287–3443 and supports the possibility of CCOs forming in binaries, with rotation playing a key role in core collapse, and the CCO XMMU J1732 being the lightest NS ever observed.